How to Kill Epsilons with a Dagger: A Coalgebraic Take on Systems with Algebraic Label Structure - Bonchi, Filippo; Milius, Stefan; Silva, Alexandra; Zanasi, Fabio (Proc. Coalgebraic Methods in Computer Science (CMCS'14), 2014)
We propose an abstract framework for modeling state-based systems with internal behavior as e.g. given by silent or -transitions. Our approach employs monads with a parametrized fixpoint operator to give a semantics to those systems and implement a sound procedure of abstraction of the internal transitions, whose labels are seen as the unit of a free monoid. More broadly, our approach extends the standard coalgebraic framework for state-based systems by taking into account the algebraic structure of the labels of their transitions. This allows to consider a wide range of other examples, including Mazurkiewicz traces for concurrent systems. © 2014 IFIP International Federation for Information Processing.
UnivIS-Import:2015-04-17:Pub.2014.tech.IMMD.profes_1.howtok